Finite Element Modelling of Sport Impacts: Brain Strains from Falls Resulting in Concussion in Young Children and Adults - Koncan, David (Université d'Ottawa / University of Ottawa, 2018)
Concussions are injuries that can result in debilitating symptoms, suffered by people of all ages, with children being at elevated risk for injury. Falls account for over 20% of head injuries worldwide, and up to 50% of concussive injuries in children. Following a concussion, children typically take longer for symptoms to resolve compared to adults. It is unknown whether or not children are more, less, or equally susceptible to concussive injury based on the mechanical response, with researchers divided on the subject. There is currently a paucity of published data for concussive injuries in children, with few studies investigating impact biomechanics and strain response in the brain using FE models. Those that exist typically rely on scaled adult models that do not capture age-dependent geometric properties, material properties of tissues, and the developmental stage of the brain reflected by the patterns of grey and white matter within the brain. Newer child models are being developed, however at present they are focused on car crash investigations that do not offer an accurate reflection of sports-related impacts, and those that could be experienced from day-to-day activities since impact characteristics (e.g. magnitude, duration, surface compliance) differ largely between these types of events. Strain magnitudes differ between events causing concussion in adults (falls, collisions, punches, and projectiles), so it follows that the unique impact characteristics of car crash events do not typically coincide with those associated with sports impacts. Car crash events can result in much longer impact durations compared to sporting impacts (100 ms duration in car crashes vs. 5-30 ms in sports impacts). The purpose of this thesis was to assess how the mechanical response of the brain in young children near 6 years old differs from an adult brain in cases resulting in concussive injury for sports impacts. Study one created a novel FE model of a 6-year-old brain, using medical images to extract an accurate representation of the geometry and tissues inside the head of a 6-year-old child. The developmental stage of the younger brain was captured using a highly-refined mesh to accurately represent the folds of white matter within the cerebrum. With no intracranial data for child cadavers available, published data of adult cadavers was used to validate the brain motion from impacts. Comparisons were made to a scaled adult model to highlight how the different model constructions influence brain motion and resulting strains. The new model showed higher correlation to the cadaver data compared to the scaled model, and yielded “good biofidelity” measures when assessed using a modified version of the normalized integral square error method. For young children, the new model was proposed to be more appropriate for concussion investigations as it captures age-appropriate geometry, material properties, and developmental stage of the brain, reflected in the patterns and volumes of grey and white matter within the brain. Study two tested the model for sensitivity across three levels of surface compliance and impact velocity consistent with sport impact events, and compared strain responses to a scaled adult model. The 6-year-old model showed unique strain responses compared to the scaled adult model with peak strains being lower across most impact events. Strain patterns also differed between models, with less strain being transmitted into the white matter in the 6-year-old model. Low compliance impacts yielded highest differences in strains (~30%), moderate compliance impacts yielded more similar strains (~9% lower), with high compliance impacts showing a location dependent response with frontal impacts being 14% lower, and side impacts being 9% higher than the scaled model. The sensitivity study characterized the model responses, allowing for better comparisons between the two different model constructions. Study three then compared the strain responses of reconstructed real-world concussive events for both children and adults. Forty cases of concussion from falls in children and adults (20 children aged 5-7, 20 adults) were reconstructed using physical models, with the measured impact kinematics used to load the FE models. Concussive cases of children showed lower strains than adults, finding a velocity driven relationship since the child concussions occurred at lower impact velocities compared to the adults. Lower peak strains, as well as cumulative strains in the child cases suggest that children are vulnerable to concussion at lower strain compared to adults. Protective strategies for children should address this vulnerability, no longer relying on product scaling to create head protection for youth.
Keywords: Concussion; Child head injury; Finite element modelling; Brain injury